Vocabulary Instruction In Improving Students' Reading Comprehension In SD Negeri 8 Menteng Palangka Raya - Ramyola Arisha Wianie; Misrita Misrita; Natalina Asi (Journal on Education, 2023)
One of the most important lessons in elementary school is understanding what they read. While reading comprehension is essential to academic success, not all students demonstrate adequate proficiency. The researcher interviewed and observed classes in SD Negeri 8 Menteng Palangka Raya, notably sixth grade, and found this issue. The researcher utilized one of the instructions to promote reading comprehension from that issue. Vocabulary instruction could increase English text comprehension, according to the study. This semester, students studied Describing People and Objects and picked descriptive text. The researcher solved the challenge with a quasi-experimental non-equivalent control group design. This study had two groups: 6A (control) and 6C (experimental). The experimental group randomly sampled vocabulary training, while the control group received non-vocabulary education. There were also two variables in this study: vocabulary teaching served as the independent variable, and the mean scores of both groups' tests served as the dependent variable. Pre- and post-test results determined the class's vocabulary instruction effectiveness. Finally, the data showed that vocabulary instruction improves reading comprehension more than non-vocabulary instruction. Scores were less than 0.05, rejecting H0 and accepting Ha. Data less than 0.05 indicates that independent variables only partially impact the dependent variable. Vocabulary education improves students' reading comprehension in SD Negeri 8 Menteng Palangka Raya